Thomas Hardy: his career as a novelist - Millgate, Michael (Macmillan, 1994)
This work of Hardy criticism has been revised and makes use of Hardy's own manuscripts, notebooks and letters, and of the correspondence and reminiscences of those who knew him. The author seeks to resolve the "work/life dichotomy" by pursuing the "unitary conception of a career".